Visualizing Innovative Student Support Services to Promote Literacy in Distance Education - Haque Nawaz (IJLTP, 2025)
The objective of this study was to explore students’ perceptions regarding the new initiatives of Allama Iqbal Open University (AIOU) in student support services to promote literacy in distance education. This used survey method and data was gathered from students of the teacher training program bachelor’s in education (B.Ed. 1.5 years) through questionnaire. The sample was 33% of the total enrollment of 1555 students. Data was collected through mail and personally by the research. Findings of the study revealed that students perceived that ICT has made their study process easier and more convenient. Timely receipt of course related information from the university kept them motivated to persuade their studies. However, the learners showed their concern about non-responsive attitude from the staff for attending telephone calls, non-awareness regarding financial assistance schemes in rural and far-flung areas and delay and non-receipt of books well in time. It was concluded that there was no significant difference among the students about the AIOU new initiatives regarding admissions, mailing, tutorials, examinations, library, web services and call center. However, students of rural and urban areas perceived those new initiatives regarding examination differently. It was recommended that improved and effective use of ICT is imperative to strengthen the student support services in open distance learning in future to enhance literacy activities’ outreach. It was also recommended that apart from printed material, the availability of books online may be ensured.